The Use of “Nursery Rhymes” as Strategy to Enrich Students’ Vocabulary of the Forth Graders - Meylia, Riska; Resta Permana, Dio; Nur Iman, Jaya (CV. Ulil Albab Corp, 2025)
This study investigated by the low vocabulary levels of fourth-grade students at IGM Elementery School Palembang, which leads to difficulties in reading comprehension and effective communication. The aim of this research was to examine the effectiveness of using nursery rhymes to improve students' vocabulary. The research design used in this study was Classroom Action Research (CAR). The sample of this research was class of IV B consisted of 24 students. The data were gathered through qualitative and quantitative data. Based on the result of this research showed that there was a development on the students’ vocabulary mastery, it can be seen from the mean score of pretests were 63.8, the mean score of posttest cycle 1 was 73.6 and the mean score of posttest cycle 2 was 91.7. In addition, there were 9 students (37.5%) who passed minimum mastery criterion in the pretest. Meanwhile, in cycle 1, there were 13 students (54.1%) who passed minimum mastery criterion, and it gained which was in the posttest cycle 2 there were 24 students (100%) who passed minimum mastery criterion, so the criteria of success were achieved. Then, from the result of observation indicated increased student activity and participant in the teaching-learning process during the implementation of nursery rhymes.